2021
DOI: 10.4314/ijs.v22i3.18
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistant Escherichia coli among patients with gastrointestinal tract infections seeking health care services at Lafia, Nigeria

Abstract: Gastrointestinal tract (GIT) in human plays an important role in providing habitat to various microbial communities including numerous prokaryotic cells numbering over 100 trillion. This study was aimed at accessing the multidrug resistance (MDR) of E. coli among patients with GIT infections seeking health care at Dalhatu Araf Specialist Hospital (DASH), Lafia, Nasarawa state, Nigeria. A total of one hundred and fifty (150) stool samples were collected using sterile sample containers from patients with symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…The resistance to Ciprofloxacin is comparable to the study of Malik et al (2021) that reported resistance rate of 73.6% to Ciprofloxacin. However lower resistance rate of 24.5% and 17.8% to Ciprofloxacin was reported by Ya'aba et al (2020) and Najim et al (2019). Resistance to Nalidixic acid is comparable to results of Sharma et al (2013) and Wagle et al (2018) who reported resistance rates of 78.9% and 71.5% respectively.…”
Section: Multiple Antibiotic Resistance Index (Mari) Of Escherichia C...supporting
confidence: 66%
See 1 more Smart Citation
“…The resistance to Ciprofloxacin is comparable to the study of Malik et al (2021) that reported resistance rate of 73.6% to Ciprofloxacin. However lower resistance rate of 24.5% and 17.8% to Ciprofloxacin was reported by Ya'aba et al (2020) and Najim et al (2019). Resistance to Nalidixic acid is comparable to results of Sharma et al (2013) and Wagle et al (2018) who reported resistance rates of 78.9% and 71.5% respectively.…”
Section: Multiple Antibiotic Resistance Index (Mari) Of Escherichia C...supporting
confidence: 66%
“…This is in contrast to various other studies where higher resistance rate was recorded. Engda et al (2018) and Najim et al (2019) reported that E. coli isolates were totally resistant (100%) to amoxicillin-clavulanic acid while Ya'aba et al (2020) and Malik et al (2021) reported resistance level of 61.22% and 81.1% to amoxicillin-clavulanic acid respectively. Lower resistance rate to Amoxicillin/clavulanic acid observed in this study could be due to the effectiveness of the drug combinations.…”
Section: Multiple Antibiotic Resistance Index (Mari) Of Escherichia C...mentioning
confidence: 99%